2022
DOI: 10.4236/ajps.2022.1312100
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Anaemic Activity and Potential Toxicity of Extracts of Four Tinctorial Plants Used in the Treatment of Anemia in Benin: <i>Gossypium barbadense, Sorghum bicolor, Hibiscus sabdariffa</i> and <i>Justicia secunda</i>

Abstract: Justicia secunda, Sorghum bicolor, Gossypiun barbadense and Hibiscus sabdariffa are dye plants traditionally used in Benin for the treatment of anemia. This work is part of the therapeutic valorization of dyes from these plants. Its objective is to characterize their composition in chemical groups and evaluate their harmlessness and their anti-anaemic property in laboratory rats. Anemia was induced in Wistar rats by phenylhydrazine hydrochloride followed by treatment by gavage with hydroethanolic extracts of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…This decrease in HCT was reversed by treatment with C. juncea which is consistent with the study of Sheth et al The mean HCT significantly increased in females treated with 200 and 400 mg/kg of A. vera whole leaf extract (16) . The recovery of the hematocrit level is favored by the administration of the plant extracts tested, the highest recovery rate being that induced by J. secunda (97.87%) followed by nearly S. bicolor (93.95%) then G. barbadense (87.41%) and H. sabdariffa (80.35%), on the 18th day of treatment (17) . This, effect may be due to protective effect of C. juncea against phenylhydrazine-induced hemolysis.…”
Section: Blood Parametermentioning
confidence: 95%
“…This decrease in HCT was reversed by treatment with C. juncea which is consistent with the study of Sheth et al The mean HCT significantly increased in females treated with 200 and 400 mg/kg of A. vera whole leaf extract (16) . The recovery of the hematocrit level is favored by the administration of the plant extracts tested, the highest recovery rate being that induced by J. secunda (97.87%) followed by nearly S. bicolor (93.95%) then G. barbadense (87.41%) and H. sabdariffa (80.35%), on the 18th day of treatment (17) . This, effect may be due to protective effect of C. juncea against phenylhydrazine-induced hemolysis.…”
Section: Blood Parametermentioning
confidence: 95%
“…37 The anti-anaemic properties of S. mombin could very much connected to its phytochemical constituents. 38 Anti-cancer activity Plants and plant-based products usage are of positive therapeutic importance when used in therapy for cancer and tumour-related diseases. A study conducted by Metibemu and others revealed the © 2024 the authors.…”
Section: Methodsmentioning
confidence: 99%
“…The phytochemicals detected in the methanolic extract of Irvingia gabonensis, as shown in Table 1, have also been seen in plants that possess anti anaemic effects (35,36). This provides a correlation between this study and previous studies.…”
Section: Sciences Of Pharmacymentioning
confidence: 97%